Implementation of Countermeasures Effort of Illegal Fishing in Indonesia (Case Study on Sinking the FV Viking Vessel) - Tarigan, Muhammad Insan (Faculty of Law, Universitas Negeri Semarang, 2018)
Geographically almost 70% of Indonesian territory consists of waters that potentially storing an amazing wealth of the sea, and the biggest is on fisheries sector. Illegal fishing that was done by foreign vessels in Indonesian territorial waters was estimated giving loss to Indonesia around 1 million ton/year (Rp 30 trillion/year). Indonesian government has decided to take policy in doing sinking illegal fishing vessels for the actors of illegal fishing in Indonesia. How is the relevance of international law with the law on sinking foreign vessels in Indonesia and the implementation on the regulation of sinking FV Viking Vessel. The research on this paper is normative legal research, and research method library research also documenter not only to the primary sources but also to secondary sources that related with the problem on this research. After the identification and classification process, the problem will be normatively analyzed using the data. Illegal fishing is not only affecting the economy aspect but also affecting the other aspects, such as state sovereignty, social, as well as environmental of the sea. The law of sinking illegal fishing vessels is not contradicting and still considered relevant with International law, either UNCLOS 1982, IPOA-IUU Fishing or CCRF. An FV Viking vessel was caught by TNI AL working with Norwegian Interpol at Indonesian ZEE. FV Viking vessel was entering to Indonesian territory without doing the obligation to reporting their identity and the navigation data. Moreover, this vessel does not have the License on Fishing. The sinking vessel is better not using the bombing method but using the method of burning the vessels with oil fuels thus it will be more cost saving. Sinking illegal fishing vessels is supposed to be done after there is a judgment from the court.